Das deutsche Eisenbahnsystem ist in Leipzig auf die Welt gekommen. 170 Jahre europäische Eisenbahnmagistrale Leipzig-Dresden. - Haase, Ralf (Deutscher Verkehrs-Verl., 2009)
Die Entwicklungsgeschichte der Menschheit ist auch die Geschichte des Verkehrs. Eine terrestrische Ortsveränderung von Gütern und Personen geschah über Jahrtausende überwiegend nur im lokalen bzw. regionalen Rahmen. Erst mit der Erfindung der Eisenbahn mittels Rad-Schiene-Technik und Dampfmaschine im Prozess der industriellen Revolution entstand ein leistungsfähiges Massenverkehrsmittel, welches eine zukunftsgerechte Mobilität gewährleistete und heute unter modernen technologischen Aspekten eine Renaissance erlebt.

The festive opening of Germany's first long haul railway between Leipzig and Dresden, on 7 April 1839, was based on a plan developed by Friedrich List. It served as a major incentive for the subsequent construction of steam-powered railways across Germany. Some four years after the commissioning of Germany's first 6 km long railway - based on an English model - between Nuremberg and Fürth, this first long haul rail link distinguished itself by technical pioneering achievements and a high degree of profitability. It served as the starting point for an all-German railway system based on the design concepts of List. The industrial revolution proceeded in the form of a close working relationship with the construction and operation of the railways, which thus made a contribution to Germany's evolving capitalist economic order. Railways actually helped to prepare the way for the political unification of Germany in 1871. The well-developed rail network of that time nowadays constitutes the Central European sector ofthe trans-European rail system in the EU.
Celebrating 170 years of Europe's railway trunk route Leipzig-Dresden.
Keywords: Verkehr; Eisenbahn; Eisenbahnverkehr; Verkehrsinfrastruktur; Verkehrsanlage; Trassierung; Verkehrstechnik; Verkehrspolitik; Industrialisierung; Wirtschaftsentwicklung; Verkehrsgeschichte; Wirtschaftsgeschichte